Management and Pedagogical Practices in Tinoc National High School: Perspectives of Teachers and Students - TUGUINAY, MARY MAVIS (Azal Arts and Humanities, 2026)
This study examined the management and pedagogical practices in Tinoc National High School from the perspectives of teachers and students. Using a descriptive research design, data were gathered through survey questionnaires administered to selected teachers and students to assess perceptions of school management practices and classroom pedagogy. The findings revealed that school management practices were generally perceived as effective, particularly in instructional leadership, communication, and supervision. These practices provided a supportive environment that enabled teachers to implement effective classroom instruction. Results further showed that teachers employed varied pedagogical strategies and maintained effective classroom management, which promoted learner engagement and active participation. Students reported improved understanding of lessons and greater involvement in classroom activities. The alignment between management support and pedagogical practice contributed to a positive teaching–learning environment despite challenges related to limited instructional resources. The study concludes that effective school management plays a vital role in strengthening pedagogical practices and enhancing learner engagement. The findings underscore the importance of sustained instructional leadership and continuous support for teachers to improve teaching and learning outcomes in secondary schools. Keywords: school management, pedagogical practices, instructional leadership, learner engagement,